The Treaty of Lisbon and the European Union as an actor in international trade - Woolcock, Stephen (ECIPE BrusselsBE, 2010)
Discusses the changes that the Treaty of Lisbon will introduce to European Union external trade policy decision making. Provides an initial assessment of how the Treaty might affect the role of the EU as an actor in international trade.